2017
DOI: 10.1016/j.cell.2017.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Influence of 3′-End Structures on Mammalian mRNA Processing and Stability

Abstract: SUMMARY The physiological relevance of structures within mammalian mRNAs has been elusive, as these mRNAs are less folded in cells than in vitro and have predicted secondary structures no more stable than those of random sequences. Here, we investigate possibility that mRNA structures facilitate the 3′-end processing of thousands of human mRNAs by juxtaposing poly(A) signals (PASs) and cleavage sites that are otherwise too far apart. We find that RNA structures are predicted to be more prevalent within these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 40 publications
6
120
1
Order By: Relevance
“…In addition, recently published results suggest that genetic variants could affect APA regulation also in an indirect way, without affecting the regulatory machinery. Past studies have reported that a narrow range of 10-30nt between the PAS and the poly(A) site is required for efficient processing, however [73] suggested that also greater distances can sometimes be used thanks to RNA folding events that bring the PAS and the poly(A) site closer to each other. Therefore, we can speculate that if a genetic variant affects RNA folding in such a way as to modify the distance between the PAS and the poly(A) site, it could also influence APA regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recently published results suggest that genetic variants could affect APA regulation also in an indirect way, without affecting the regulatory machinery. Past studies have reported that a narrow range of 10-30nt between the PAS and the poly(A) site is required for efficient processing, however [73] suggested that also greater distances can sometimes be used thanks to RNA folding events that bring the PAS and the poly(A) site closer to each other. Therefore, we can speculate that if a genetic variant affects RNA folding in such a way as to modify the distance between the PAS and the poly(A) site, it could also influence APA regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The PAS motif is always located upstream of its target poly(A) site. It has been suggested that a narrow range of 10-30 nt is required for efficient processing, but recent work suggests that also larger distances can be functional thanks to RNA folding processes bringing the poly(A) site closer to the PAS [73]. Assuming that a PAS-altering SNP would affect the usage of its nearest poly(A) site, we associated to each intragenic SNP the nearest downstream poly(A) site, selected those for which such poly(A) site was located within the PRE/POST segments, and retained as candidate variants only those whose distance from the corresponding poly(A) site was between 10 and 100 nt.…”
Section: Cis Regulatory Domainsmentioning
confidence: 99%
“…To search for motifs associated with rapid turnover, miRNAs were either ranked according to half-life or classified into fast-and slow-turnover subsets. To search for position-specific motifs, a list of miRNA sequences ranked by half-life was supplied to kpLogo (Wu and Bartel 2017). To query differences in more general nucleotide content, miRNAs were classified as fast or slow turnover.…”
Section: Motif and Feature Searchesmentioning
confidence: 99%
“…As a result, such functional structures would have been missed by conventional methods that rely on covariation. Bartel and colleagues showed that random structures in the 3’UTR are required for mRNA stability (Wu and Bartel, 2017). This study highlights the limits of conventional comparative sequence analysis and the need for direct determination of structures.…”
Section: Conservation Analysis Of the Rna Structuresmentioning
confidence: 99%